When darkness ends - Ivy, Alexandra (New York, NY : Kensington Publishing Corp., 2015)
Transported from the magical land of the feys to his desolate medieval castle, Cyn, the vampire clan chief of Ireland, meets his match in a sharp-witted fairy princess who, immune to his charms, needs his help in stopping someone from closing the veil that separates the dimensions.
Keywords: Vampires -- Fiction; Seduction -- Fiction; Man-woman relationships -- Fiction; Paranormal romance stories; Romantic suspense fiction